EARLY DETECTION STRATEGY OF IMPLEMENTING HEALTH PROMOTION MODELS TOWARD CERVICAL CANCER EVENTS IN BRATI PUSKESMAS AREAS - Festy Mahanani Mulyaningrum; Anita Lufianti; Yuwanti Yuwanti (Universitas PGRI Semarang, 2020)
The incidence rate of cervical cancer in Central Java is 9.2%. Based on reports from health service agencies in Central Java, there were 7,029 cases in 2017 and in 2018 there were 7,029 cases. Early detection of cervical Ca with the IVA method in Central Java developed since 2007 the incidence of cervical cancer can be reduced by early detection. The purpose of this study was to determine the extent of the influence of health promotion, husband's support and information sources on early detection of cervical cancer, as well as the effective and relative contributions. This type of research uses quantitative research with a cross sectional approach, while the sampling technique is saturated sampling (census) where all members of the population are used as the research sample. The results of this study indicate a significant relationship between husband's support, health promotion, counseling with early detection of cervical cancer.